The role vitamin-C on phagocytosis of macrophage on C. albicans. - Melok Tin Melok Tin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Several studies reported that vitamin-C can enhance immune response, including phagocytosis response on bacteria and virus. However at present there are only a few studies about the role of vitamin-C in phagocytosis response on fungi.Objectives: To determine the role of vitamin-C on macrophage phagocytosis on C. albicans.Methods: Ten ml blood was taken from healthy subject. Buffy coat containing monocytes was separated from the red-blood cells. After plating the mononuclear cells on the coverslip glass, the cells other than monocytes were washed out by tripsinization. The monocytes were treated with several doses of vitaminC i.e. 200 mg/mL, 100 mg/mL, 50 mg/mL, and 0 mg/mL as placebo. And then Candida suspension was added to the cells, stained PAS and HE counterstain. The result of macrophage phagocytosis activity was interpreted by counting intracellular Candida spores and was analyzed using one way ANOVA.Result: There is a high significant difference in the. number of intracellular candida spores, between vitamin-C 200 mg/mL compared to placebo (p<0.000); and there wasn't significant difference between 100mg/mL (p=0.064) and 50 mg/mL (p=0.709) compared to placebo.Conclusion: The dose of 200 mg/mL vitamin-C could increased macrophage phagocytosis activity on C.a/bicans significantly (p<0.01) compared to other doses. Key word: phagocytosis - macrophage - vitamin-C - C. a/bicans